Tonga : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This paper describes economic developments in Tonga during the 1990s. From 1993 to 1996, financial policies were quite expansionary. Following the licensing of two new banks, credit growth accelerated in 1994. The National Reserve Bank of Tonga initially adopted an accommodating stance, but in December 1995, tightened monetary policy significantly. Hampered by its poor profitability in the use of indirect monetary instruments, it relied on an increase in reserve requirements. Meanwhile, fiscal policy had added further to demand pressures with the recurrent budget surplus declining, owing to a cost-of-living adjustment to government wages.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet